Training on making Nata de coco at SMA Kesatrian 1 Semarang - Erwin Nofiyanto; Sudjatinah Sudjatinah; Sri Budi Wahjuningsih (Universitas Muhammadiyah Magelang, 2022)
Nata de coco business development has good economic potential. Nata de coco is a low-calorie snack whose fiber can aid physiological processes. It has an appealing aroma and can be prepared in a variety of flavors, and it lasts a long time. The nata de coco snack was chosen as the training material because it can be prepared with simple processing technologies, making it simple to execute for students. The purpose of the program for SMA Kesatrian 1 Semarang students is to strengthen their business skills. Lectures, debates, and practices are used to carry out the program method. The program's results reveal that students understand and can produce nata de coco, as well as the different types of nata. Students believed that the nata-making course was quite beneficial in increasing their excitement for entrepreneurship.